A longitudinal study of Type-B aortic dissection and endovascular repair scenarios: computational analyses - Chen, Duanduan; Müller-Eschner, Matthias; Kotelis, Drosos; Böckler, Dittmar; Ventikos, Yiannis; Tengg-Kobligk, Hendrik von (Medical engineering & physics, 2013)
Conservative medical treatment is commonly first recommended for patients with uncomplicated Type-B aortic dissection (AD). However, if dissection-related complications occur, endovascular repair or open surgery is performed. Here we establish computational models of AD based on radiological three-dimensional images of a patient at initial presentation and after 4-years of best medical treatment (BMT). Computational fluid dynamics analyses are performed to quantitatively investigate the hemodynamic features of AD. Entry and re-entries (functioning as entries and outlets) are identified in the initial and follow-up models, and obvious variations of the inter-luminal flow exchange are revealed. Computational studies indicate that the reduction of blood pressure in BMT patients lowers pressure and wall shear stress in the thoracic aorta in general, and flattens the pressure distribution on the outer wall of the dissection, potentially reducing the progressive enlargement of the false lumen. Finally, scenario studies of endovascular aortic repair are conducted. The results indicate that, for patients with multiple tears, stent-grafts occluding all re-entries would be required to effectively reduce inter-luminal blood communication and thus induce thrombosis in the false lumen. This implicates that computational flow analyses may identify entries and relevant re-entries between true and false lumen and potentially assist in stent-graft planning.